The communicative betting towards the rationality of Habermas's critical libertarianism as a model - gueroui, imane (Journal of Social Sciences and Humanities, 2021)
This research sheds light on the deep debate that has taken place in contemporary German philosophy in particular on the issue of modernity and the enlightening mind as the Frankfurt School undertook to formulate a critical theory to question and criticize the Western Enlightenment philosophical project We want to shed lightin this article on the epistemological turn in the history of European thought and a good example that we can supply In this article, the contemporary critical theory aroused by the German philosopher Jurgen Habermas, as he is considered one of the most prominent contemporary German philosophers, it is no less important than the great German philosophers through the ages as it is called the bright mind of the Frankef School She saw Habermas defended modernity and described it as an unfinished project, using communicative openness, a general theory of society in which he combined philosophy and sociology. Likewise, Habermas suggested activating philosophical thinking in producing liberal critical reasoning based on rebuilding the requirements of the mind by replacing the conceptual framework The religious mind of the communicative mind It has expanded its philosophical critical project among many of its books, including an example without limitation: The theory of communicative action 198010